Clinical profile of viral hepatitis in a tertiary health care centre of eastern India - Behera, A.K; Jit, B.P; Purohit, P; Nahak, S.R; Chhatar, S; C, Marndi; Mohapatra, M.K; Bag, S (International Journal of Medical Research and Review, 2016)
Background: Viral hepatitis is epidemic to developing country like India. Infection with Hepatitis A virus, Hepatitis B virus and Hepatitis C virus is much more important so far as the disease severity, selection of treatment option and adverse outcome associated with the therapy is concerned. This study was undertaken to assess the clinical and laboratory profile of viral hepatitis with co-infection at a tertiary care centre. Material and Methods: Patients admitted in the hospital with presenting signs and symptoms of viral hepatitis were included. The clinical and haematological profiles were observed and entered in a pre-designed format. Data were extracted and analysed by one-way-analysis-of-variance (ANOVA) and p < 0.05 was considered statistically significant. Results: The mean age of the patients was 32.86±13.3 years (range, 18-60 years). Eleven patients were positive for hepatitis-E where as 6 patients were co-infected with both hepatitis-A and hepatitis-E. The commonest presenting symptom was yellowness of eyes and urine that accounts in 19 patients followed by fever in 8 patients, abdominal pain in 5 patients and vomiting in 3 patients. The incidence of dengue and leptospirosis was found in one patient each. Two patients had died. Conclusion: Large cohort of patients with different hepatitis virus infections is necessary for better understanding of pathophysiology, clinical profile that will enable treatment regimen tools for the patients for single as well as different co-infection.